Molecular diagnostics and ITS-based phylogenic analysis of Streptococcus suis serotype 2 in central Vietnam - Bach Hoang Nguyen; Dieu Hong Nu Phan; Hien Xuan Nguyen; An Van Le; Alberto Alberti (Journal of Infection in Developing Countries)
Introduction: Streptococcus suis (S. suis) serotype 2 has recently become the most prevalent cause of meningitis in adults in many areas of Vietnam. This study provides data on S. suis molecular diagnosis in central Vietnam using a real-time polymerase chain reaction (PCR) assay targeting the S. suis serotype 2 cps2J gene. Additionally, 16S-23S rDNA intragenic spacer (ITS)-based phylogenic analysis of strains isolated from cerebrospinal fluid (CSF) in Thua Thien Hue Province, Vietnam, is presented and discussed. Methodology: Pathogenic bacteria were isolated from 40 CSF samples, and 18 were identified as S. suis by culture-dependent methods. Capsular serotyping was assessed by real-time PCR. ITS sequences were obtained after traditional PCR and were used in phylogenic analyses. Results: Pathogenic bacteria were isolated from 36 out of 40 CSF samples. A total of 18 S. suis strains were isolated and assigned to serotype 2 by real-time PCR. One CSF sample, negative when tested by culture-dependent methods, was positive to S. suis serotype 2 by real-time PCR. Pairwise alignments of the 18 ITS sequences did not reveal any variable nucleotide position, and resulted in a single sequence type. Sequences were similar to S. suis serotype 2 reference ITS sequences (> 98.1%), and there was no lack of an ITS spacer region in the isolates. Conclusions: S. suis serotype 2 is the most prevalent serotype in central Vietnam. Real-time PCR assay proved to be a reliable diagnostic method for early detection of S. suis 2 in CSF samples.